Impairments in sleep and brain molecular clearance in people with cognitive deterioration and biological evidence of AD: a report of four cases - Mariateresa Buongiorno; Esther Granell; Giovanni Caruana; Gemma Sansa; Yolanda Vives-Gilabert; Natalia Cullell; Jessica Molina-Seguin; Marta Almeria; Cristina Artero; Gonzalo Sánchez-Benavides; Nicola J Ray; Sonia A.L. Correa; et al. (BMC Neurology, 2023)
Abstract Background Recent evidence suggests that the failure of the glymphatic system – the brain’s waste clearance system, which is active during sleep – plays a key role in the pathophysiology of Alzheimer’s Disease (AD). Glymphatic function can be investigated using serial MRIs after intrathecal gadobutrol injection. This technique can reveal the health of the glymphatic system, but has not yet been used in participants with cognitive impairment due to AD. Case report This report describes the sleep and gadobutrol tracer clearance patterns of four participants diagnosed with mild to moderate cognitive impairment with evidence of AD pathology (pathological levels of Ab and p-tau in cerebrospinal fluid). We performed polysomnography and MRI studies before tracer injection and MRI scans at 1.5-2 h, 5–6 h, and 48 h after injection. Despite participants reporting no sleep problems, polysomnography revealed that all participants had moderate to severe sleep disturbances, including reduced sleep efficiency during the study and obstructive sleep apnea. Severe side-effects related to tracer administration were observed, impeding the completion of the protocol in two participants. Participants who finished the protocol displayed delayed and persistent tracer enrichment in the cortex and white matter, even 48 h after injection. These outcomes have not been observed in previous studies in participants without AD. Conclusion The findings suggest that brains with sleep impairment and AD pathology have poor glymphatic function, and therefore cannot clear the contrast tracer efficiently. This is likely to have caused the severe side effects in our participants, that have not been reported in healthy individuals. Our results may therefore represent the only available data acquired with this technique in participants with AD pathology.